(3GdEdeGe HCMGOjK GdCMcGes - (3eMeO Hf Ydj Hf hgH Hf eWjY, GHf Objb GdYjO , Jbj GdOjf GdbTjQj CHh GdaJM,J (B702 (3g` s
(3ChdgG (B:s
(3GdMeO ddg efRd GdTQGFY hGdCMcGe hHYO agPG eNJUQ ai Yde GdMOjK JCedJ ebUhOg JCedkG , hde COY GdGMGOjK hSejJg HcJGHg GdEdeGe HCMGOjK GdCMcGe s
(3BNQgG (B:s
(3abGdhG (B: (3He fSejgG ? bGd (B: (3SehgG RjfH , hai Gdfgi Yf GdJSejI HHQI hHYO gPG , hJe GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG Jedc HGSe eMeO Hf CMeO GdZjWi GdTGaYi hJGQjNI jQLY dSfI (B966 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B70s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B158s
Keywords: (3GdMOjK h GdeUWdMs